Environment, Media, and Popular Culture in Southeast Asia
X, 348 p. 45 illus., 40 illus. in color.
Keywords: This book addresses the increasingly important subject of ecomedia by critically examining the interconnections between environment, ecology, media forms, and popular culture in the Southeast Asian region, exploring methods such as textual analysis, thematic analysis, content analysis, participatory ethnography, auto ethnography, and semi-structured interviewing. It is divided into four sections: I. Activism, Environment, and Indigeneity; II. Political, Ecologies and Urban Spaces; III. Narratives, Discourses, and Aesthetics; and IV. Imperialism, Nationalism, and Islands, covering topics such as broadcast media (radio and TV) and the environment; green cinema and ecodocumentaries, ecodigital art, digital environmental literature. It is of great interest to researchers, students, practitioners and scholars working in the area of humanities, media, communications, cultural studies, environmental humanities, environmental studies, and sustainability.